Effect of bariatric surgery on asthma control, lung function and bronchial and systemic inflammation in morbidly obese subjects with asthma - van Huisstede, Astrid; Rudolphus, Arjan; Castro Cabezas, Manuel; Biter, Laser Ulas; van de Geijn, Gert-Jan; Taube, Christian; Hiemstra, Pieter S; Braunstahl, Gert-Jan (Thorax, 2015)
BackgroundThe pathogenesis of asthma in obese subjects is poorly understood and has been described as a specific phenotype in these patients. Weight loss improves asthma control and lung function. Whether this improvement is the result of better mechanical properties of the airways or decreased systemic and bronchial inflammation remains unclear.MethodsA longitudinal study in obese patients with asthma (bariatric surgery and asthma group (BS+A), n=27) and obese control (bariatric surgery without asthma group (BS−A), n=39) subjects undergoing bariatric surgery, and obese patients with asthma without intervention (no bariatric surgery and asthma group (NBS+A), n=12). Lung function, asthma control, cellular infiltrates in bronchial biopsies and circulating markers of systemic inflammation were measured during follow up at 3, 6 and 12 months.ResultsBariatric surgery resulted in a profound weight loss at 12 months. In the BS+A group as well as the BS−A group FEV1, functional residual capacity, total lung capacity improved, whereas FEV1/FVC only improved in the BS−A group. In addition, Asthma Control Questionnaire (ACQ), Asthma Quality of Life Questionnaire, inhaled corticosteroid use and PD20 improved in BS+A, whereas in the NBS+A group only ACQ improved. Small airway function R5–R20 improved in both surgery groups, however the change in the BS+A group was greater, resulting in a comparable R5–R20 between BS+A and BS−A at 12-month follow-up. Besides improvement of systemic inflammation (high sensitivity C-reactive protein, adiponectin and leptin) after BS, only a decrease in mast cell numbers was detectable in the BS+A group.ConclusionsBariatric surgery improved small airway function, decreased systemic inflammation and number of mast cells in the airways. These effects could explain the improvement of asthma control, quality of life and lung function. Therefore bariatric surgery, in addition to all other positive effects, also improves asthma in subjects with morbid obesity.Trial registration number3204.